Pengaruh Fee Audit, Rotasi Audit, Reputasi Auditor dan Spesialisasi Auditor terhadap Kualitas Audit - Famelya Ayuni; Dian fitria handayani (Jurnal Buana Akuntansi, 2023)
This study aims to examine the effect of audit fees, audit rotation, auditor reputation and auditor specialization on audit quality in transportation sub-sector companies listed on the Indonesian stock exchange in 2018 to 2021. The population in this study was 47 transportation sub-sector companies that listed on the Indonesian stock exchange from 2018 to 2021. Sampling uses purposive sampling, namely sampling by setting certain criteria. Based on the criteria that have been set so that a sample of data is obtained as many as 29 companies in the transportation sub-sector for an observation period of four years, a sample of 116 data is obtained. In this study, the data analysis used was descriptive statistical analysis and logistic regression analysis. The results of this study indicate that audit fees have a significant and positive effect on the audit quality of transportation sub-sector companies listed on the Indonesian stock exchange in 2018 to 2021. While audit rotation, auditor reputation and auditor specialization have no effect on audit quality of transportation sub-sector companies that are listed on the Indonesian stock exchange. listed on the Indonesian stock exchange from 2018 to 2021.